Strategic Sourcing and Competitiveness in Supermarkets. A Case of Abrah Supermarket - Emmaculate Wangeci Mwangi (Uganda Christian University, 2024)
The research was undertaken to investigate on strategic sourcing and competitiveness in supermarkets. It was guided by three objectives; to assess the effect of supplier relationships on competitiveness in supermarkets, to analyze the effect of risk management on competitiveness in supermarkets, to determine the effect of supply chain management on competitiveness in supermarkets. The researcher used a sample size of 40 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective shows that supplier relationships positively (Beta=0.153) predicts the competitiveness in supermarkets and effect is significant at p-value < 0.05. by 9.9%, Results of the second objective reveals that tax risk management on positively (Beta=0.224) predicts the competitiveness in supermarkets and effect is significant at p-value < 0.05. by 7.8% while results of the third objective show that supply chain management (Beta=0.091) predicts and affects their competitiveness in supermarkets. However, its effect is insignificant at p-value > 0.05 by 3.5%. It can be concluded that supplier relationships have a significant effect on competitiveness in supermarkets, risk management has a significant effect on competitiveness in supermarkets and lastly supply chain management have a significant effect on competitiveness in supermarkets. There is need Abrah supermarket to regularly communicate with suppliers to maintain a strong relationship. Keep them updated on sales data, inventory levels, and upcoming promotions. This will help them plan their production and ensure the timely delivery of products. Work together with suppliers to forecast demand and plan production accordingly. Sharing information about upcoming promotions and sales targets can help suppliers prepare in advance and ensure they have sufficient inventory. Negotiate competitive pricing, payment terms, and discounts with suppliers. This can help reduce costs and increase profitability, making the supermarket more competitive.
Undergraduate Research